Surgical management of tibial metastases: a systematic review. - Greco, Tommaso; Fulchignoni, Camillo; Cianni, Luigi; Maccauro, Giulio; Perisano, Carlo (Acta Biomedica Atenei Parmensis, 2022)
Background: Tibia is a rare location among all skeletal metastases. Those lesions are often discovered in an advanced stage of disease and are mainly reported to the orthopedic surgeon to reduce pain, to improve the patient quality of life and his functional status. Current literature on the surgical management of metastases and/or pathological tibial fractures shows mostly few case reports, case series or at most retrospective studies on very small and heterogeneous groups of patients. The purpose of this study is to analyze those articles highlighting epidemiology and discussing surgical options and relative outcomes. Methods: Studies were searched on PubMed, Google Scholar and Web of Knowledge from inception to September 2020 and 30 articles discussing tibial metastasis surgical treatment were included. Results: Results discuss age and sex of patients, location of tibial metastases, origin of metastases, type of lesion and spread of disease, surgical treatment, outcomes in terms of pain evolution, gain of function and general status, complication and relapse, and survival of patients. Conclusions: Despite the lack of randomized trials and the absence of high-level studies, guidelines suggest different types of treatments depending on location and stage of disease. The analysis of the articles included in this review confirms the heterogeneity of possible treatments, assuring, independently of the chosen techniques, good and similar results, leading to the conclusion that the choice of the surgical technique must take in consideration each patient’s characteristics and the surgeon’s experience.